Peso ao nascer no estado do Pará: uma abordagem nutricional entre os anos - 1996 a 2016 - FARIAS, Rayane Mayra da Silva (2023)
Objective: To know the weight of the live births of the births of women residing in Pará from 1996 to 2016. Method: Epidemiological study of the transverse type using secondary data from DATASUS / MS. The following variables were studied: numbers of live births / year, birth weight, maternal age, number of prenatal consultations, gender and mesoregions of the State of Pará. Results: The total number of live births in the years studied was 2,862,070, of which 47.17% were the majority male gender and 46.07% female. The number of live births increased from 2011 to 2016 (29.45%). With regard to maternal age, the majority had 20 years or more. Regarding the number of prenatal visits, up to 6 visits (40.68%) prevailed. Conclusion: In the state of Pará in the period from 1996 to 2016, there were 2,862,070 live births, with a gradual increase during the period studied, with the male gender prevailing.